PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VII MTsS DINIYAH PANDAI SIKEK - Savitri, Siska; Emidar, Emidar; Rasyid, Yulianti (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
ABSTRACTÂ The purpose of this study is to describe the influence of cooperative learning model of Think Talk Write in writing exposition text at grade VII ofMTsS Diniyah Pandai Sikek. The method of this research is an experimental method with a quasi experiment type. The result of this research shows that there is an influence of cooperative learning model of think talk write in writing exposition text for students at grade VII at MTsS Diniyah Pandai Sikek at significant level 95% with degree of freedom (n1+n2) -2, that is ttable<tvalue(1,70 <7,48). Ho is rejected and H1 is accepted because the results of testing the hypothesis prove that the value of ttabel is smaller than tvalue.Â Kata Kunci: pengaruh, kooperatif, think talk write, teks eksposisi.